2017
DOI: 10.1115/1.4037845
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation on Mechanical and Wear Properties of Al7075/SiCp Composites: Effect of SiC Content and Particle Size

Abstract: One of the major advantages of metal matrix composites (MMCs) is that their tailorable properties meet the specific requirements of a particular application. This paper deals with the experimental investigations done on the effects of the reinforcement particulate size and content on the Al7075/SiC composite. The composites were manufactured using stir casting technique. The effect of SiC particle size (25, 50, and 75 μm) and particulate content (5, 10, and 15 wt %) on the microstructural, mechanical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…The maximum hardness was 169.5 BHN by cumulative reinforcement of 15wt.% B 4 C and CSFA particles in aluminum alloy. Similar results were found in the fly ash particle reinforced composites, which improved hardness of the aluminum matrix composite [28][29][30][31] . Overseas Foundry Earlier research results also revealed [28,30] that the aluminium alloy with reinforcement particles like boron carbide and fl y ash reinforcement offered maximum tensile strength as compared to the unreinforced Al alloy.…”
Section: Hardnesssupporting
confidence: 84%
“…The maximum hardness was 169.5 BHN by cumulative reinforcement of 15wt.% B 4 C and CSFA particles in aluminum alloy. Similar results were found in the fly ash particle reinforced composites, which improved hardness of the aluminum matrix composite [28][29][30][31] . Overseas Foundry Earlier research results also revealed [28,30] that the aluminium alloy with reinforcement particles like boron carbide and fl y ash reinforcement offered maximum tensile strength as compared to the unreinforced Al alloy.…”
Section: Hardnesssupporting
confidence: 84%
“…Surface quality improved in turning of AlSi7Mg2-MMC samples when cutting speed decreased. Rao et al [12] have done an experimental investigation on mechanical properties of Al7075/SiC-p composites and they found that by increasing SiC particle size and wt. % considerably enhanced the tensile strength and hardness of the composites but the ductility of the composite is decreased.…”
Section: Effect Of Sic Reinforcement On the Mechanical Properties Of mentioning
confidence: 99%
“…% of SiC particles in Al. Rao et al [12] have done an experimental investigation on wear properties of Al7075/SiC-p composites. AA7075 reinforced with SiC-p (particle size of 25μm, 50μm and 75μm and particulate content 5, 10 and 15wt.…”
Section: Effect Of Sic Reinforcement On the Abrasive And Sliding Wearmentioning
confidence: 99%
“…Composite materials play an important role in engineering applications because of numerous specialized applications in aerospace and auto-motive industries due to their high strength-to-weight ratio, good fatigue and creep resistance, a high coefficient of thermal expansion, excellent wear resistance, and good machinability. [1]- [3]. A combination of two or more materials that differ in shape or addition on a large scale is called as composite material which exhibits better properties than that of the individual material [4]- [6].…”
Section: Introductionmentioning
confidence: 99%